2012
DOI: 10.1094/pdis-09-11-0807
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Brassica Host Genotypes by a Single-Spore Isolate and Population of Plasmodiophora brassicae (Clubroot)

Abstract: LeBoldus, J. M., Manolii, V. P., Turkington, T. K., and Strelkov, S. E. 2012. Adaptation to Brassica host genotypes by a single-spore isolate and population oí Plasmodiophora brassicae (clubroot). Plant Dis. 96:833-838.Plasmodiophora brassicae, the cause of clubroot of crucifers, is an increasingly important pathogen of canola (Brassica napus) in Alberta, Canada. In response, clubroot-resistant canola genotypes are being deployed to help reduce yield losses. Two experiments were conducted to examine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Also, cortical infection and the subsequent development of resting spores have been reported in several non-cruciferous plant species, such as Indian cress and beet (Beta vulgaris L.) (Ludwig-Müller et al, 1999). The cropping of resistant cultivars may stimulate resting spore germination, thereby reducing the viable spore population in the soil, while no (or few) viable resting spores will be produced on the resistant plants to contribute to soil inoculum loads LeBoldus et al, 2012).…”
Section: Baiting Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, cortical infection and the subsequent development of resting spores have been reported in several non-cruciferous plant species, such as Indian cress and beet (Beta vulgaris L.) (Ludwig-Müller et al, 1999). The cropping of resistant cultivars may stimulate resting spore germination, thereby reducing the viable spore population in the soil, while no (or few) viable resting spores will be produced on the resistant plants to contribute to soil inoculum loads LeBoldus et al, 2012).…”
Section: Baiting Cropsmentioning
confidence: 99%
“…However, none of these cultivars are immune to clubroot . A proportion of the plants of each cultivar develop small galls under high inoculum pressure in the field (LeBoldus et al, 2012). These infected plants may be the result of segregation or incomplete gene penetrance, or may represent the first stage of pathogen adaptation to the resistance gene(s) in these cultivars.…”
Section: Resistancementioning
confidence: 99%
“…Pathotype 7 was predominant and in both Poland and the Czech Republic, representing around 43-44 % of the studied populations. The differences between the countries were even greater when the pathotype classification was based on the threshold of ID < 50 % with CI of 95 %, as described by LeBoldus et al (2012). In this case, there were eight pathotypes in Poland and six in the Czech Republic, with only five in common to both countries.…”
Section: Discussionmentioning
confidence: 91%
“…For ID 25 %, there were nine and 10 pathotypes in Poland and the Czech Republic, respectively, with only one (16/14/31) common to both countries. Based on an ID < 50 % with the 95 % CI not exceeding 50 % (LeBoldus et al 2012), 15 pathotypes in total were identified, with four in common: 16/2/14, 16/14/12, 16/14/15 and 16/31/8. The most common pathotype was 16/14/15 and it constituted over 23 % of the whole population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation